Shifts in Community Benefits Spending Among Nonprofit Hospitals in Nebraska and 10 Proximate States, 2012 and 2015. Issue 1 (January 2022) - Palm, David; Pacino, Valerie; Grimm, Brandon
Abstract : Context: Federal and state policy makers have debated the evolving concept of community benefit and the extent to which nonprofit hospitals are providing benefits to the community in exchange for the tax benefits they receive. Objective: This study compares community benefits spending by nonprofit hospitals in Nebraska and other selected states in both 2012 and 2015. Expenditures are also examined by rural, regional, and urban hospitals within Nebraska. Methods: Community benefit expenditure data were taken from Community Benefit Insight and consolidated into the categories of direct patient care, community health improvement initiatives, and health professions education and research. Results: When community benefit expenditures were compared across 11 states, Nebraska had the highest percentage of expenditures for community health improvement initiatives in both 2012 and 2015. Although community benefit expenditures for the 44 nonprofit hospitals within Nebraska increased from 2012 to 2015, they remained flat as a share of total hospital expenditures. In 2015, 63% of community benefit expenditures were allocated to direct patient care, which represented a 7.3% decrease from 2012. This decline led to greater spending on community health improvement initiatives (3.1%) and health professions education and research (4.2%). Rural, regional, and urban hospitals spent more proportionately on community health improvement initiatives in 2015 than in 2012. Conclusions: The shift in community benefit expenditures from direct patient care to community health improvement initiatives and health professions education and research suggests that hospitals are investing in programs with broader community-wide benefits. Nebraska allocates a significantly larger share of its community benefits spending to community health improvement activities than other Great Plains and Midwestern states. Nebraska is in the process of implementing Medicaid expansion, which may shift future community benefits spending decisions. Abstract : Supplemental Digital Content is Available in the Text.